TRANSFORMASI PRAKTIK RUANG REDAKSI MEDIA ALKHAIRAAT ONLINE PALU - Ayu Abd. Aziz (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
This research aims to uncover and interpret the process of media transformation through the practice of Palu's online Alkhairaat media newsroom (MAL). This research uses qualitative methods with ethnographic approaches. Research data is obtained through interviews, documentation and field records. Allows researchers to experience routines and interact with journalists in the newsroom. Data analysis is focused on the process of transformation by applying media convergence, particularly to work culture in newsroom practice. The results showed that the transformation process that took place in the editorial room of Alkhairaat media (MAL) online by applying media convergence, namely: (1) Full digitization, where the process of production and distribution of news in Alkhairaat media becomes fully digital. (2) The work culture in the newsroom changes the deadlines and rhythms of journalists' work to be faster. Editorial meetings are conducted online, where journalists, designers, editors collaborate in one online news content production space. There is also a process of sharing content between MAL and Radio Alkhairaat, both of these media under ownership. Share content in the form of re-pack. (3) MAL editors convergecontent, news is presented in multimedia form combined in the form of text, images, audio and video.